Modern Views on Various Aspects of the Psychological Health of Adolescents - Yermukhanova, Lyudmila Sergeevna; Nazarbayeva, Rysty Kaztyganovna; Sultanova, Gulnar Dostanovna; Izimbergenova, Gulmira Namazovna; Tazhbenova, Saule Tazhedinovna; Knissarina, Malika Maksatovna; Aitmaganbet, Perizat Zhaksibayevna (Journal of Intellectual Disability - Diagnosis and Treatment, 2019)
Objectives: The purpose of this article is to study and generalize, detect main tendencies in modern views on various aspects of the psychological health of adolescents in recent publications (taken into account the publication on multiple problems of adolescents’ health over the past decade: 2009-2019). Method: The literature search was conducted using Medline, TRIP Database and Cochrane Library to identify relevant medical studies over the past 10 years (2009-2019). The keywords search and title search and advanced search were applied in order to determine the articles and other forms of surveys on the general topic of adolescents’ psychological health. The articles were filtered for the TOP-30 concerning chronological principle and their actuality, novelty, citation level and deepness of the researchable aspect. Results: Multiple publications that focus on the psychological health of adolescents were detected. They concentrate on the principal factors that force pathological psychical behaviour among adolescents. E.g., the impact of family members' health and life-limiting conditions, unemployment and precarious employment, the negative impact of alcohol and the Internet, cognitive-behavioral therapy programs, the internalization of symptoms in depressive or anxious states, Internet-based therapy, responses to antidepressants, the Youth Version Short (EQ-i: YV-S) have been described. The chosen medical studies have been systemized in the form of a table and some of them were discussed more closely due to their importance and novelty. Conclusions: The study generalizes the most modern and innovatory views on aspects of the psychological health of adolescents in international publications taking into account synchronic and diachronic notions. The study may be used for close browsing of the current state of investigations in this scientific area as well as for further investigations in the forms of surveys and clinical experiments take notice of already detected and undetected yet problems.